Metaphor and metonymy in grammaticalization processes: the case of "aí" marker of specificity - Tavares, Maria Alice (2009)
From the theoretical framework provided by functional linguistics, in this article I present some proposals regarding metaphorical and metonymic extensions of meanings in grammaticalization processes. I claim that one of these proposals applies to the case of the grammaticalization of “aí” as a marker of specificity in indefinite nominal phrases: the proposal which supports that metaphorical extension and metonymic extension can occur together in grammaticalization processes. As a marker of specificity, “aí” is generally used when the speaker wants to show that the identity or properties of what is being referred to are not relevant to the hearer. Besides, “aí” can show negative appreciation, qualifying the core noun of the indefinite nominal phrase as being something wrong or with low quality. Based on semantic and pragmatic properties of different usages of “aí”, I propose a grammaticalization trajectory, probably followed by it, from spatial deictic meanings to the use as a marker of specificity in indefinite nominal phrases. Metaphorical and metonymical extensions play an important role in this trajectory.